2010
DOI: 10.1371/journal.pone.0010735
|View full text |Cite
|
Sign up to set email alerts
|

Deletion Mutants of VPg Reveal New Cytopathology Determinants in a Picornavirus

Abstract: BackgroundSuccess of a viral infection requires that each infected cell delivers a sufficient number of infectious particles to allow new rounds of infection. In picornaviruses, viral replication is initiated by the viral polymerase and a viral-coded protein, termed VPg, that primes RNA synthesis. Foot-and-mouth disease virus (FMDV) is exceptional among picornaviruses in that its genome encodes 3 copies of VPg. Why FMDV encodes three VPgs is unknown.Methodology and Principal FindingsWe have constructed four mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…An investigation has shown non-structural protein 2C, 3A, and VPg as key determinants for modulating cytopathology in cell culture [29]. In fact, the replacements either in 2C or 3A are associated with altered virulence, cell tropism or host range in several picornaviruses [23,[30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…An investigation has shown non-structural protein 2C, 3A, and VPg as key determinants for modulating cytopathology in cell culture [29]. In fact, the replacements either in 2C or 3A are associated with altered virulence, cell tropism or host range in several picornaviruses [23,[30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…We typically use BSR-T7 cells since they grow faster than the parental BHK clone line. Cells are infected with fowlpox (FPV) encoding for T7 RNA polymerase (FPV-T7) 18 which functions as a helper virus to drive expression of the viral RNA and subsequent recovery of infectious virus (Figure 4). Although BSR-T7 cells constitutively express T7 RNA polymerase, this expression is not sufficient to rescue infectious MNV after transfection of pT7:MNV 3'Rz in the absence of helper FPV-T7.…”
Section: Direct Recovery Of Infectious Mnv From Cdna In Cells Expressmentioning
confidence: 99%
“…However it is worth noting that new preparations of helper virus grown in primary fibroblasts are functionally titrated to determine the dose required for efficient virus recovery. Protocols for the propagation and titration of FPV-T7 have been previously described 18 . 3.…”
Section: Direct Recovery Of Infectious Mnv From Cdna In Cells Expressmentioning
confidence: 99%
“…However, they also found that viruses lacking 3B3 were not viable and proposed that this was due to aberrant processing at the novel 3B2/3C junction generated by deleting 3B3 [49]. Subsequently, Pacheco et al [55] and Arias et al [56] reported that viruses lacking both 3B1 and 3B2 were viable, with the former study reporting normal growth phenotypes in BHK-21 cells. Arias et al went on to suggest that although a virus with a single 3B had near normal RNA replication in BHK-21 cells, virus particle release was severely compromised [56].…”
Section: Introductionmentioning
confidence: 99%